World Bicycle Relief : social enterprise business model - Van Mieghem, Jan A. (SAGE Knowledge. Cases., 2018)
In this case, students assume the roles of FK Day and Dave Neiswander, leaders of the social enterprise World Bicycle Relief (WBR), which donates and sells bicycles in sub-Saharan Africa. As a social enterprise, WBR combines not-for-profit and for-profit activities. Starting as a traditional not-for-profit organization formed to donate bicycles after the Indian Ocean tsunami in 2004, WBR eventually added a for-profit arm to facilitate growth and reduce its dependence on donations and grants. As a result, by 2017 WBR had distributed around 400,000 bicycles, primarily to schoolgirls, entrepreneurs, and health workers. As the organization grows, its leaders are interested in optimizing operations and entering new countries in Africa. What is the optimal distribution of WBR's resources between its for-profit and not-for-profit operations? How should it define the objective of its operations: should WBR maximize its social impact or the total number of bicycles in the field? Which countries should it enter?